Pengaruh Profitabilitas, Solvabilitas, Auditor Switching, dan Ukuran Perusahaan Terhadap Penyelesaian Audit (Audit Delay) (Studi Empiris Pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Periode 2017-2021) - Rizki Amalia; Indupurnahayu Indupurnahayu (Komunitas Dosen Indonesia, 2024)
This study aims to determine the effect of profitability, solvability, auditors switching, and company size in manufacturing companies in the various industrial sectors listed on the Indonesia Stock Exchange (IDX) for the 2017-2021 period. The research method used in this study is a quantitative approach using a descriptive method in which the results of research data are in the form of presentation of statistical results obtained using Eviews 12 software. This research uses secondary data. Sampling using technique purposive sampling and there are 21 manufacturing companies in various industrial sectors with a five-year period. Based on the analysis that has been carried out in this study, the results show that the influence of the profitability and solvability variables is a significant negative effect on audit delay, then the auditor switching variable has a significant positive effect and firm size does not have a significant effect on audit delay. Thus, companies that have good profitability and solvability will reduce audit delay because management will speed up the publication of financial reports. Then the change of auditors will extend the audit delay because the new auditor must adapt again to company conditions, and the size of a company size must pay attention to audit delay because it will attract investors, and avoid sanctions.